2011
DOI: 10.2105/ajph.2011.300227
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Changes in Dental Care Coverage on Dental Care Utilization Among Retirees and Near-Retirees in the United States, 2004–2006

Abstract: Objective To examine dental utilization transition dynamics between 2004 and 2006 in the context of changing dental coverage status with data from the Health and Retirement Study (HRS) for persons ages 51 years and older. Methods We estimate a multivariable model of dental use transitions controlling for dental coverage and retirement transitions and other potentially confounding covariates. Results We find that elderly persons losing dental coverage between the 2004 and 2006 survey periods were more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…In oral health, patients reporting outcomes using different dental services (Anderson et al, ; Brennan et al, ), patients' experiences of oral health related to quality of life after dental treatments (Allen, Savadatti, & Gurmankin Levy, ; Tsakos et al, ) and changes in dental coverage status in relation to oral status (Manski et al, ) were found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In oral health, patients reporting outcomes using different dental services (Anderson et al, ; Brennan et al, ), patients' experiences of oral health related to quality of life after dental treatments (Allen, Savadatti, & Gurmankin Levy, ; Tsakos et al, ) and changes in dental coverage status in relation to oral status (Manski et al, ) were found.…”
Section: Resultsmentioning
confidence: 99%
“…Situational transitions mainly regarded conditional changes focusing on caregivers (Cook, Pierce, Hicks, & Steiner, 2006;Eriksson & Sandberg, 2008), out-of-home care such as foster care (Daining & DePanfilis, 2007), becoming a professional (Johnstone, Kanitsaki, & Currie, 2008;Yan, Gao, & Lam, 2013), professional practices (Höjer & Sjöblom, 2011) or retiring (Jonsson, 2011;Manski et al, 2011).…”
Section: Typologies Of Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore not surprising that both wealth and income have a strong and independent positive effect on dental-care use among the elderly 9 . Similarly, it is not surprising that having dental insurance coverage, which lowers the out-of-pocket cost of care, also increases the likelihood of dental-care use 10,11 .…”
Section: Financial Factorsmentioning
confidence: 99%
“…Earlier work found that older individuals with higher household wealth holdings were more likely to seek dental care, even controlling for insurance coverage and household income (9). Previous work has also shown that lower levels of household income are associated with a lower likelihood of older adults newly seeking dental care and a higher likelihood of stopping dental care (10). Thus, it stands to reason that changes in household wealth and income associated with the outset of the recent recession may also be important determinants in the decision to seek dental care among older adults.…”
Section: Introductionmentioning
confidence: 99%